2006
DOI: 10.1097/01.rlu.0000227490.63768.d1
|View full text |Cite
|
Sign up to set email alerts
|

Fibroid Uterus Confounding the Correct Localization of Active Gastrointestinal Bleeding During Tc-99m RBC Scan

Abstract: The unexpected visualization of the normal or pathologic uterus has been reported in the radionuclide imaging literature. Occasionally, this may create a diagnostic dilemma during interpretation of Tc-99m RBC scans, bone scans, or renal scans and additional imaging modalities are usually necessary to further define the abnormality. We report an interesting case of fibroid uterus identified as an intense, heterogeneous, and persistent vascular pelvic mass during a Tc-99m RBC scan in a patient with concomitant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Further limitations include lack of immediate availability, notably during on call hours, and subjectivity to false positive localization of a bleed due to tagged blood moving within the GI lumen during peristalsis (23) or position changes in the context of various non-GI pathologies e.g., uterine fibroids (24). The overall positive yield of red cell studies is reported to be ~50% (23).…”
Section: Diagnosismentioning
confidence: 99%
“…Further limitations include lack of immediate availability, notably during on call hours, and subjectivity to false positive localization of a bleed due to tagged blood moving within the GI lumen during peristalsis (23) or position changes in the context of various non-GI pathologies e.g., uterine fibroids (24). The overall positive yield of red cell studies is reported to be ~50% (23).…”
Section: Diagnosismentioning
confidence: 99%
“…In addition, variable uterine activity during the ovulatory cycle causes fixed increased perfusion due to endometrial proliferation (76). Finally, a uterine leiomyoma may show transient, fixed activity due to hypervascularity (77)(78)(79).…”
Section: Increased Rbc Activity Due To Other Causesmentioning
confidence: 99%
“…11 Many potential false-positive findings can occur in the 99m Tc-RBC bleeding, including arteriovenous malformation, 12 pelvic kidney, 13 hepatic hemangioma, 14 dilated mesenteric veins, 15 varices, [16][17][18] gallbladder in patients with renal failure, 19 and aortic aneurysm. 20 It is well-known that uterus in a woman who is pregnant, 21 shortly postpartum, 22 or having fibroid 23 can have elevated 99m Tc-RBC activity during the gastrointestinal bleeding scintigraphy. Our case further indicates that a detailed clinical history including menstrual status should be taken as part of the prestudy procedure in aiding accurate interpretation of 99m Tc-RBC bleeding study in childbearing age of women.…”
mentioning
confidence: 99%